Feline Trichomonosis - ทุมพงษ์, จิตรบรรจง (Journal of Mahanakorn Veterinary Medicine, 2019)
Feline trichomonosis, a large bowel disease in domestic cats caused by Trichomonas foetus, is now prevalent in many parts of the world. The disease can cause asymptomatic infection in cats or chronic diarrhea which mainly occurring in kittens. T. foetus is a protozoan parasite which has long been recognized as a causative agent of bovine trichomonosis, a disease of cattle reproductive system. While bovine trichomonosis is a venereal disease in cattle, feline trichomonosis is thought to transmit by faecal-oral route. This review article provides concept knowledge of the disease in cats, the disease transmission, diagnosis and treatment.